2022
DOI: 10.52589/ajafs-c0442z7j
|View full text |Cite
|
Sign up to set email alerts
|

Post Harvest Losses and Food Security in Nigeria: An Empirical Review

Abstract: Given the renewed impetus by the Nigerian Government to diversify the economy through improvement in agricultural productivity, there is the need to put in place measures that will ensure that the anticipated increase in production will not result in colossal waste. Towards this end, this paper examines critically the causes and extent of post-harvest loss in Nigeria and strategies that should be put in place to reduce such loss. The underlying assumption is that reduction in post-harvest loss will ensure impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…For example, in Nigeria, post-harvest losses of essential crops such as grains, tubers, and fruits are a pressing issue. A study published by Oyinlola (2018) reported that post-harvest losses in Nigeria can be as high as 50% for some food items. These losses not only contribute to food insecurity but also result in reduced nutrient availability for the population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Nigeria, post-harvest losses of essential crops such as grains, tubers, and fruits are a pressing issue. A study published by Oyinlola (2018) reported that post-harvest losses in Nigeria can be as high as 50% for some food items. These losses not only contribute to food insecurity but also result in reduced nutrient availability for the population.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, one of the largest economies in the region, post-harvest losses have been a significant concern. According to a study published Aliyu (2017), post-harvest losses for major crops like maize, rice, and cassava can range from 20% to 50%. These losses not only result in economic setbacks for farmers but also lead to reduced nutrient availability in the food supply chain.…”
Section: Introductionmentioning
confidence: 99%